Origin and development of drug addiction in South Asia with special reference to Pakistan - Abdul Malik; Syeda Farhana Sarfaraz (Pakistan Journal of Commerce and Social Sciences (PJCSS), 2011)
During the course of this search man has extracted opium from poppy plant, cocaine from the leaves of coca bush, and cannabis from the hemp plant. Initially the use of these was only for the purpose of relieving the physical and mental capabilities, and for medicinal and surgical purpose. But the human spirit of innovation must have led to the use of these substances for mood-altering effects and offer an escape from the real and difficult world of existence to a more agreeable world of fantasy. These things are perhaps a few of the oldest natural substances a fewer of the oldest natural substances used by human race. The major purpose of the study is to highlight the origin and development of the drug addiction in the South Asian region, and discover its impacts on Pakistan. The problem of the drug addiction, which once could be learned as a by-product of drug trafficking throughout Pakistan has become a major challenge for the governments, philanthropists and the social reformers of this age. The present extent of addiction depicts a bleak future for the generation to come, unless a revolutionary, well-coordinated and determined approach is envisaged and implemented.
Keywords: 330; Drug Addiction; Drug Trafficking; South Asia; Pakistan